High throughput screening for human disease associated-pathogens and antimicrobial resistance genes in migratory birds at ten habitat sites in China - Lan Wang; Ru Jia; Rufei Ma; Jie Li; Shanrui Wu; Yeshun Fan; Dan Zhao; Dianfeng Chu; Yihua Wang; Guogang Zhang; Jie Liu (BMC Microbiology)
Abstract Background Migratory birds have been found to carry and spread pathogens, contaminating the environment and causing diseases in humans and other animals. To our knowledge, there hasn’t been any systematic targeted screening for known pathogens in migratory birds. In the current study, customized real time PCR based TaqMan Array Cards (TAC) were used to detect 99 human disease related pathogens and 20 antimicrobial resistance (AMR) genes in migratory birds at 10 habitat sites in China. Results The results showed that 30.5% (107/351) of migratory birds carried at least one of 14 pathogens. The most prevalent pathogens included Aeromonas, Plasmodium, Cryptosporidium, Giardia lamblia, enteropathogenic Escherichia coli (EPEC), Campylobacter jejuni/coli, and Rickettsia. Their distribution demonstrated certain host or region specificity. Anseriformes carried higher rate of pathogens (39.1%, 72/184) than Charadriiformes (23.2%, 33/142, p < 0.05). The overall pathogen detection rate was the highest in Hubei (87.1%, 27/31), possessing exclusively Anser. The pathogen quantities were estimated to be 103 to 2 × 108 gene copies per gram of feces. AMR genes associated with resistance to macrolides, quinolones, tetracyclines, and β-lactams were widely detected, with overall quantities ranging from 105 to 109 copies of interrogated genes for each drug class per gram of feces. Conclusions Using such a multi-target detection and quantification platform, this study evaluated the potential role of migratory birds as reservoirs or vectors for a broad range of pathogens and AMR genes in the environment, indicating their capacity to transmit zoonotic diseases. These might provide evidence for implementation of targeted intervention with a one health approach.